Fibrinolytic activity and vascular access inchronic renal failure patients under haemodialysis - Costa, Elísio (2008)
Our aim was to study the relationship between fibrinolytic activity and the type of vascular access in haemodialysis patients. We measured the circulating antigen levels of plasminogen activator inhibitor type-1 (PAI-1), tissue plasminogen activator (tPA) and D-dimers. This study was performed in 50 CRF patients under regular haemodialysis, 11 with central venous dialysis catheter and 39 with AV-fistula, and in 25 healthy controls. Compared with controls, CRF patients presented significantly lower levels of tPA and with higher levels of D-dimers. In CRF patients, the levels of D-dimers correlated positively and significantly (r=0.359, p=0.01) with rhEPO doses (rhEPO/Kg/week) and negatively with haemoglobin levels (r=-0.335, p=0.017). When comparing the two groups of CRF patients, we found that those with central venous catheter vascular access presented a statistical significant rise in D-dimer and tPA plasma levels. No difference was found between the two groups of patients concerning the plasma levels PAI-1. Our results showed an altered haemostasis in CRF patients, as suggested by the rise in D-dimer, an index of fibrin turnover and intravascular thrombogenesis. The increased levels of D-dimer and tPA in CRF patients, particularly in those using central venous dialysis catheters, led us to propose a relationship between the type of vascular access chosen for the haemodialysis procedure, and the risk of thrombogenesis. It seems reasonable to assume that these patients present an increased risk for cardiovascular disease events.